« Zombie Blairites » in a « Momentum plot »: The Political Polarisation of the British Labour Party over a Local Regeneration Scheme in The Guardian and The Observer - Marie-Pierre Vincent (Amnis)
The British Labour Party, under its 2015-2020 leader, Jeremy Corbyn was harshly divided between the Corbynites at the head of the party, supporting radical left-wing views, and the local Blairite councillors, supporting moderate views. This political antagonism hardened in Haringey, a London council, over a regeneration scheme, revealed to the nation by The Guardian in 2017. It was indirectly framed as a political polarisation in two left-leaning national newspapers (The Guardian and The Observer). Drawing on Critical Discourse Analysis conducted on a corpus of thirty-five press articles, this paper aims at discussing how the media coverage of this local issue in these two press organs reflected the political polarisation of the Labour Party under Corbyn’s leadership.